Autoestima y la conducta alimentaria en adolescentes de 15 a 18 años de la Unidad Educativa Réplica “Eugenio Espejo” de la ciudad de Babahoyo - Avecillas Borrero, Flor Shirley (2025)
Self-esteem is fundamental for each individual, since it influences the way they perceive themselves, whether positively or negatively, and can affect their daily lives, especially adolescents where self-concept is important to them, for example. Therefore, Eating Disorders (ED) is a relevant factor that can be affected by self-esteem since eating behaviors are serious mental illnesses that are related to altered behavior regarding eating habits, which translates into behaviors ranging from eating uncontrolled to the lack of food intake, which mainly affects adolescents and young women and its appearance is mainly influenced by biological and personality factors. The present research study with a quantitative approach with a correlational scope and a non-experimental design deal with self-esteem and eating behavior in adolescents from 15 to 18 years of age from the “Eugenio Espejo” Replica Educational Unit in the city of Babahoyo. Therefore, the object of this research is to evaluate self-esteem and its relationship with eating behavior in adolescents aged 15 to 18 years from the Réplica Eugenio Espejo educational unit in the city of Babahoyo. The population of this study is 318 students, which was obtained as a sample of 174 adolescents, which refers to an intentional non-probabilistic sampling due to the affinity we have with the participants and the willingness to collaborate. To achieve the purpose of the research, bibliographic sources were used for the aforementioned variables. Two psychometric tests were applied, which are the Rosenberg self-esteem scale and the EAT-26 (Eating Attitudes Test), to measure self-esteem and the level of risk. of eating disorders